Platelet count during course of cardiogenic shock - Schupp, Tobias; Rusnak, Jonas; Forner, Jan; Dudda, Jonas; Bertsch, Thomas; Behnes, Michael; Akın, Ibrahim (ASAIO journal, 2024)
The study investigates the prognostic value of the platelet count in patients with cardiogenic shock (CS). Limited data regarding the prognostic value of platelets in patients suffering from CS is available. Consecutive patients with CS from 2019 to 2021 were included at one institution. Firstly, the prognostic value of the baseline platelet count was tested for 30-day all-cause mortality. Thereafter, the prognostic impact of platelet decline during course of intensive care unit (ICU) hospitalization was assessed. A total of 249 CS patients were included with a median platelet count of 224 × 106/ml. No association of the baseline platelet count with the risk of 30-day all-cause mortality was found (log-rank p = 0.563; hazard ratio [HR] = 0.879; 95% confidence interval [CI] 0.557-1.387; p = 0.579). In contrast, a decrease of platelet count by ≥ 25% from day 1 to day 3 was associated with an increased risk of 30-day all-cause mortality (55% vs. 39%; log-rank p = 0.045; HR = 1.585; 95% CI 0.996-2.521; p = 0.052), which was still evident after multivariable adjustment (HR = 1.951; 95% CI 1.116-3.412; p = 0.019). Platelet decrease during the course of ICU hospitalization but not the baseline platelet count was associated with an increased risk of 30-day all-cause mortality in CS patients.